Kolaborasi Guru dan Orang Tua dalam Penguatan Karakter Anak Usia Dini pada Era Digital di TK Mukti Tama - Lina; Lora Wahyuni; Afrinovera; Eka Penti Ernitasari (PT. Penerbit Tiga Mutiara, 2026)
Early childhood education faces complex challenges in the digital era because children’s interaction with technology influences their habits and character development. This condition requires continuity of education between schools and families, while collaboration between teachers and parents in strengthening character and managing children’s digital experiences still requires further investigation. This study aims to analyze forms of collaboration, communication, assistance, supervision, character habituation, supporting and inhibiting factors, and the use of technology at TK Mukti Tama. The study employed a qualitative approach with a case study design involving six observations, interviews with ten informants, and documentation. Data were analyzed through data condensation, data display, conclusion drawing, and verification using source and method triangulation. The results indicate that collaboration is carried out through routine communication, meetings, parenting programs, character habituation, and WhatsApp. The strengthened character values include discipline, responsibility, honesty, independence, politeness, cooperation, and environmental awareness. The findings emphasize the importance of continuity of values, role modeling, habituation, digital guidance, and joint evaluation in strengthening children’s character consistently and purposefully in their daily lives.